2021
DOI: 10.3390/plants10071299
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization of Phoradendron bollanum and Viscum album subs. austriacum as Mexican Mistletoe Plants with Antimicrobial Activity

Abstract: In Mexico, mistletoes have several applications in traditional medicine due to the great variety of compounds with biological activities that have not been characterized to date. The goals of the present study are to analyze the composition of minerals and phytochemical compounds in Mexican mistletoes Phoradendron bollanum and Viscum album subs. austriacum qualitatively and quantitatively, identify the compounds using HPLC-MS, and assess the antimicrobial potential in phytopathogenic microorganism control. Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…As in L. cuneifolia, PA were also found in adult plants of the Mexican mistletoes Phoradendron bollanum and Viscum album subsp. austriacum [34]. HPLC results were consistent with a previous spectrophotometric analysis; leaves and stems showed the highest levels of total polyphenolics, especially in the post-fruiting stage, where catechin was the predominant compound.…”
Section: Discussionsupporting
confidence: 89%
“…As in L. cuneifolia, PA were also found in adult plants of the Mexican mistletoes Phoradendron bollanum and Viscum album subsp. austriacum [34]. HPLC results were consistent with a previous spectrophotometric analysis; leaves and stems showed the highest levels of total polyphenolics, especially in the post-fruiting stage, where catechin was the predominant compound.…”
Section: Discussionsupporting
confidence: 89%
“…From 1940 and 2014, approximately 55% of antitumoral drugs approved for cancer treatment came from natural resources [3]. As a prominent example, Viscum album L. (white-berry or European mistletoe) is widely studied [4,5], since it presents a great variety of bioactive compounds [5] and an irrefutable therapeutic potential [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the high content of ferulic and quinic acids might be associated with the antioxidant P. brachystachyum response to the oxidative burst defense mechanism provoked by its host, Prosopis juliflora [ 32 ]. Furthermore, a study by García-García et al [ 35 ] on Phoradendron bollanum showed the vast diversity of quinic acid esters in caffeoylquinic and feruloylquinic acids; however, the authors did not quantify the metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to mention that tannins are among the phytochemicals commonly found in mistletoe species and have been reported as inhibitors of digestive enzymes due to their high affinity to interacting with proteins [ 35 , 40 , 41 , 42 ]. Here, it is important to highlight that we found high content of total and hydrolyzable tannin content; so we hypothesize that some products of the partial hydrolysis of tannins are associated with the increased flavonoid content at the end of the intestinal stage of digestion [ 43 ].…”
Section: Discussionmentioning
confidence: 99%